2021
DOI: 10.3390/ijms22041532
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-Related Changes in Mood Disorders and the Immunomodulatory Role of Lithium

Abstract: Mood disorders are chronic, recurrent diseases characterized by changes in mood and emotions. The most common are major depressive disorder (MDD) and bipolar disorder (BD). Molecular biology studies have indicated an involvement of the immune system in the pathogenesis of mood disorders, and showed their correlation with altered levels of inflammatory markers and energy metabolism. Previous reports, including meta-analyses, also suggested the role of microglia activation in the M1 polarized macrophages, reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 118 publications
0
10
0
Order By: Relevance
“…Such effects have been observed for lithium in the treatment of bipolar disorder (46). The antiinflammatory potential of lithium may result from inhibition of glycogen synthase kinase-3β (GSK-3β) which further regulates cytokines production, although other mechanisms are also considered to contribute (47). However, little is known about the effects of other mood stabilizers, such as valproate or lamotrigine on cytokine levels.…”
Section: Discussionmentioning
confidence: 99%
“…Such effects have been observed for lithium in the treatment of bipolar disorder (46). The antiinflammatory potential of lithium may result from inhibition of glycogen synthase kinase-3β (GSK-3β) which further regulates cytokines production, although other mechanisms are also considered to contribute (47). However, little is known about the effects of other mood stabilizers, such as valproate or lamotrigine on cytokine levels.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, regulation of GSK3β has been implicated in antidepressant mechanisms of action and in the pathogenesis of depression [ 8 , 9 ]. GSK-3β/β-catenin cascades have been reported that play a crucial role in the onset of depressive symptoms in animal models and thus have become a target of interest for depressive symptom alleviation and elucidation of the pathogenesis of depression [ 10 14 ]. β-catenin has been reported to induce de novo synthesis of brain-derived neurotrophic factor, an important regulator of adult hippocampal neurogenesis and behavioral effects of antidepressants [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…For nearly a century, lithium (Li) has been widely used to treat acute depression, acute mania, and treatment-resistant depression [ 1 4 ]. A number of randomized controlled trials support the primary use of Li as a mood stabilizer in the maintenance care of patients with bipolar disorder (BP) [ 5 10 ]. The American Psychiatric Association (APA) [ 11 ] recommends Li to prevent manic, hypomanic, and mixed episodes and has described Li as a ‘traditional’ mood stabilizer, as opposed to the ‘new’ mood stabilizers, also known as second-generation antipsychotics, such as olanzapine, risperidone, ziprasidone, quetiapine, and aripiprazole [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in membrane fluidity decreases insulin-stimulated glucose transport. Chromium increases membrane fluidity in the presence of insulin [107].…”
Section: Properties and Applications Diabetes Mellitus And Insulin Si...mentioning
confidence: 98%